2012
DOI: 10.1007/978-3-642-34611-8_18
|View full text |Cite
|
Sign up to set email alerts
|

A 9k Kernel for Nonseparating Independent Set in Planar Graphs

Abstract: We study kernelization (a kind of efficient preprocessing) for NP-hard problems on planar graphs. Our main result is a kernel of size at most 9k vertices for the Planar Maximum Nonseparating Independent Set problem. A direct consequence of this result is that Planar Connected Vertex Cover has no kernel with at most (9/8 − ǫ)k vertices, for any ǫ > 0, assuming P = NP. We also show a very simple 5k-vertices kernel for Planar Max Leaf, which results in a lower bound of (5/4 − ǫ)k vertices for the kernel of Planar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They also propose a 5 3 -approximation algorithm for Min CVC for any class of graphs where Min VC is polynomial-time solvable. Parameterized complexity for Min CVC and Max NSIS have been studied in [23,24] while the enumeration of minimal connected vertex covers is investigated in [18] where it is shown that the number of minimal connected vertex covers of a graph of n vertices is at most 1.8668 n , and these sets can be enumerated in time O(1.8668 n ). For chordal graphs (even for chordality at most 5), the authors are able to give a better upper bound.…”
Section: Related Workmentioning
confidence: 99%
“…They also propose a 5 3 -approximation algorithm for Min CVC for any class of graphs where Min VC is polynomial-time solvable. Parameterized complexity for Min CVC and Max NSIS have been studied in [23,24] while the enumeration of minimal connected vertex covers is investigated in [18] where it is shown that the number of minimal connected vertex covers of a graph of n vertices is at most 1.8668 n , and these sets can be enumerated in time O(1.8668 n ). For chordal graphs (even for chordality at most 5), the authors are able to give a better upper bound.…”
Section: Related Workmentioning
confidence: 99%
“…They also propose a 5 3 -approximation algorithm for Min CVC for any class of graphs where Min VC is polynomial-time solvable. Parameterized complexity for Min CVC and Max NSIS have been studied in [23,24] while the enumeration of minimal connected vertex covers is investigated in [18] where it is shown that the number of minimal connected vertex covers of a graph of n vertices is at most 1.8668 n , and these sets can be enumerated in time O(1.8668 n ). For chordal graphs (even for chordality at most 5), the authors are able to give a better upper bound.…”
Section: Related Workmentioning
confidence: 99%